(untitled) (Research, Society and Development, 2020)
The use of curly and curly hair in its natural appearance is increasingly common, as many people have begun to accept the true identity of their hair and reject the straightening processes. They started searching through the internet for products and information that contributed to the care of the natural use of their hair. With consumers increasingly critical and observant, companies need more assertive marketing strategies. The following research question then arises: What are the valued aspects regarding the consumption of curly hair products in online sales companies? In this scenario, this research aims to identify the market segmentation variables used by companies that sell curly hair products, how their consumers rank and behave in relation to their online sales strategies. The methodology used for this article is classified as bibliographic, documentary and netnographic. The emergence of a niche that can influence business decisions and the economy requires a study of its relevance in the market that operates. As a result it was found that these companies segment their consumers by the curl of the hair curl, which most of them classify as adopters and interact with the market segmentation strategies used by these companies. This study made it possible to reaffirm the importance of using marketing to attract customers.